Total penile reconstruction - Pera Erro, Enrique (Cirugía del Uruguay, 1974)
Total reconstruction of penis is interesting because of the multiplicity of tecniques and methods involved, demanding resourcefulness and personal contributions from the surgeon . A revision of 9rocedures shows that ali phalloplaEties should persue 3 anatomical goals: reproduction or corpus with mono or bi-pedicled tu bes; urethn• build with tubulized grafts, especially tubulous flaps; and a glans with a sort of coronal furrow and an imitation of prepuce and frenulum in which opens a well-centred and longitudinally elongated meatus. This is aime.d at obtaining free urinary and spermatic flow; adequate sensibility and consistency, permitting intercourse and achieved by means of grafts or muscular implants or transplants which may even make erection possible. In this paper we describe a case of this type of surgery the first in our country, in which Kaplan's technique was employed, with additional · stages and technical details that made it possible to simulat prepuce-frenulum and phallus end with glans appeirence and distal central and longitudinal ovoid orífice.